2000
DOI: 10.1177/002076400004600206
|View full text |Cite
|
Sign up to set email alerts
|

How Stigmatising Is Schizophrenia in India?

Abstract: Stigma is a social devaluation of a person because of personal attribute leading to an experience of sense of shame, disgrace and social isolation. The nature of stigma in schizophrenia and its relationship to attribution was studied in one hundred and fifty-nine urban patients of Madras, India who fulfilled DSM-IV criteria for schizophrenia. The response of the primary care givers to fourteen questions on stigma and 14 on what they thought attributed to the illness was elicited. Based on the mean stigma score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
116
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(129 citation statements)
references
References 11 publications
13
116
0
Order By: Relevance
“…41,42 The stigma attached to being labelled as having mental health problems appears to be particularly high in certain cultures, for example in India, where schizophrenia is associated with low marriage prospects and a fear of rejection by neighbours. 43 There are also cultural differences in beliefs towards psychological distress. A recent study of the attitudes of black African women in London who had suffered depression found that they thought depression was less serious, more short-lasting and less amenable to treatment compared with white British women.…”
Section: Health Beliefsmentioning
confidence: 99%
“…41,42 The stigma attached to being labelled as having mental health problems appears to be particularly high in certain cultures, for example in India, where schizophrenia is associated with low marriage prospects and a fear of rejection by neighbours. 43 There are also cultural differences in beliefs towards psychological distress. A recent study of the attitudes of black African women in London who had suffered depression found that they thought depression was less serious, more short-lasting and less amenable to treatment compared with white British women.…”
Section: Health Beliefsmentioning
confidence: 99%
“…One common approach has been to study attitudes of the general population towards the mentally ill and mental illnesses (Angermeyer & Dietrich, 2006). Most of these studies are from the Western industrialized world, but there are now also a number of studies from low-and middle-income countries, confirming the picture of mental illnesses as highly stigmatizing disorders (Thara & Srinivasan, 2000;Gureje, Lasebikan, Ephraim-Oluwanuga, Olley & Kola, 2005). The consequences of stigma associated with *Corresponding author: Helia Ghanean, Department of Clinical Sciences, Division of Psychiatry, Umeå University, 901 87 Umeå, Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of stigma is devastating, especially in those developing countries where the influence of collectivistic culture is prominent (Corrigan, 2004b;Fung, Tsang, & Corrigan, 2008). Interestingly, both PCs and published studies reported that this negative view was directed more towards female psychiatric patients as opposed to male psychiatric patients (S. Lee, 2002;Thara & Srinivasan, 2000). PCs who were interviewed also tended to conceal the fact that their relatives had a mental illness in order to prevent any stigma reaction.…”
Section: Discussionmentioning
confidence: 99%